Mekanisme Penerapan Denda Keterlambatan Pembayaran Dalam Akad Murabahah Pada Koperasi Simpan Pinjam Dan Pembiayaan Syariah Baitul Maal Wa Tamwil Nusa Ummat Sejahtera Cabang Tanjungsari - Nurhana Safira Putri Wahyudi; Nanang Sobarna (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2023)
This study aims to determine the mechanism for applying late fines in murabahah contracts at the Baitul Maal wa Tamwil Nusa Ummat Sejahtera Sharia Cooperative, Tanjungsari branch (KSPPS BMT NU Sejahtera, Tanjungsari branch). The method used in this research is a qualitative descriptive approach. To obtain the necessary data using primary data techniques, namely interviews. From this study it can be seen that the mechanism for applying late fines in murabahah contracts at KSPPS BMT NU Sejahtera Tanjungsari branch is not applied to all members who are late in making installment payments, if members experience force majeure then members will not be fined. The mechanism for implementing late fines at KSPPS BMT NU Sejahtera Tanjungsari branch is appropriate because it is in accordance with the Fatwa of the National Sharia Council NO: 17/DSN-MUI/IX/2000 fatwa regarding sanctions for able customers who delay payments.